KESULITAN BELAJAR MATEMATIKA : BAGAIMANA JIKA DITINJAU DARI KEMAMPUAN NUMERIK SISWA SLB ? - Murni, Viviana; Ali, Ferdinanus Adrian; Kurnila, Valeria Suryani (JOURNAL OF SONGKE MATH, 2018)
This research aims to diagnose the difficulties learning mathematics reviewed from numerical ability of extraordinary junior high school Karya Murni Manggaraistudents. This research was qualitative research andthe sampling technique used was purposive sampling, so the subjects were 4 of students. Data were collected using test and interview. Test was used to know the types of learning difficulties in mathematics and interview was used to know factors that cause difficulties to learn mathematics. Data were analyzed by using descriptive data analysis techniques with stages : reducing data, presentation of data, conclusion, and verification.The results of this research indicate that students are still having difficulties regarding mathematics calculations, connecting concepts in accordance with existing situation, and solve the problems. These difficulties are caused by weak memory, the material being taught is not related to the student’s daily life, and the lack of procedural, conseptual, and factual abilities. Therefore, it is necessary to find a strategy that can reduce student’s difficulties learning mathematics students and can improve student’s numerical ability.